1998
DOI: 10.1021/bi981722u
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Transitions of an Unmodified tRNA:  Implications for RNA Folding

Abstract: Unmodified tRNAs are powerful systems to study the effects of posttranscriptional modifications and site-directed mutations on both the structure and function of these ribonucleic acids. To define the general limitations of synthetic constructs as models for native tRNAs, it is necessary to elucidate the conformational states of unmodified tRNAs as a function of solution conditions. Here we report the conformational properties of unmodified yeast tRNAPhe as a function of ionic strength, [Mg2+], and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 65 publications
4
63
0
Order By: Relevance
“…Many studies reported how the lack of modification in tRNA in vitro transcripts can be compensated by an increased concentration of Mg 2+ ions to obtain functional structures (Sampson and Uhlenbeck 1988;Perret et al 1990;Maglott et al 1998;Serebrov et al 1998). We illustrate here the interchangeable stabilizing role of metal binding and post-transcriptional modification on a specific tRNA tertiary interaction, the G15-C48 Levitt base pair, provided with a physicochemical explanation of the phenomenon.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies reported how the lack of modification in tRNA in vitro transcripts can be compensated by an increased concentration of Mg 2+ ions to obtain functional structures (Sampson and Uhlenbeck 1988;Perret et al 1990;Maglott et al 1998;Serebrov et al 1998). We illustrate here the interchangeable stabilizing role of metal binding and post-transcriptional modification on a specific tRNA tertiary interaction, the G15-C48 Levitt base pair, provided with a physicochemical explanation of the phenomenon.…”
Section: Discussionmentioning
confidence: 78%
“…In vitro, modified tRNAs exhibit greater thermodynamic stability than the corresponding unmodified tRNAs (Hall et al 1989;Maglott et al 1998;Serebrov et al 1998;Vermeulen et al 2005). Consistent with a role for modified nucleotides in stabilizing tRNAs, pre-tRNA Met i is unstable in cells containing a mutation in the m 1 A methyltransferase (Kadaba et al 2004).…”
Section: Introductionmentioning
confidence: 75%
“…premature aggregation of the colloid. Unfolding of tertiary structure occurs with half-lives ranging from 0.01 s as demonstrated for tRNA (Maglott et al 1998) and RNase P (Fang et al 2000(Fang et al , 2002 to at least between 3 and 35 s, as demonstrated for the Tetrahymena thermophila self-splicing intron (Bevilacqua et al 1992;Zhuang et al 2000). Thus, it is possible for the RNA to be partially unfolded during the course of the assay.…”
Section: Discussionmentioning
confidence: 95%